The relative antimicrobial effect of blue 405 nm LED and blue 405 nm laser on methicillin-resistant Staphylococcus aureus in vitro. Issue 9 (December 2015) - Masson-Meyers, Daniela; Bumah, Violet; Biener, Gabriel; Raicu, Valerica; Enwemeka, Chukuka
Abstract It has long been argued that light from a laser diode is superior to light from a light-emitting diode (LED) in terms of its effect on biological tissues. In order to shed light on this ongoing debate, we compared the antimicrobial effect of light emitted from a 405-nm LED with that of a 405-nm laser on methicillin-resistantStaphylococcus aureus (MRSA) at comparable fluences. We cultured 5 × 106  CFU/ml MRSA on tryptic soy agar and then irradiated culture plates once, twice, or thrice with either LED or laser light using 40, 54, 81, or 121 J/cm2 fluence at 15-, 30-, or 240-min time interval between irradiation. Cultures were incubated immediately after irradiation at 37 °C for 24 h before imaging and counting remnant bacterial colonies. Regardless of the device used, LED or laser, irradiation at each fluence resulted in statistically significant bacterial growth suppression compared to non-irradiated controls (p  < 0.0001). The antimicrobial effect of both light sources, LED and laser, was not statistically different at each fluence in 35 of the 36 experimental trials. Bacterial growth suppression achieved with either source of light increased with repeated irradiation, particularly at the 15- or 30-min treatment time interval. Thus, we conclude that the antimicrobial effect of 405-nm laser and 405-nm LED on MRSA is similar; neither has a superior antimicrobial effect when compared to the other.